Book Review - CAPITAL IN THE 21ST CENTURY, BY THOMAS PIKETTY - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2016)
Only few books of economy in the recent past years have had a similar effect on public opinion as the work of Professor Thomas Piketty from Paris School of Economics, in which he attempts to explain the dynamics of the last two centuries income inequality in developed countries. Shortly after the release of the English version, appeared excellent reviews from some major economists like Robert Solow, Paul Krugman, Robert Shiller, all three Nobel Prize winners, as we all know. "It is the most important book of the century" concluded Esquire magazine, and Paul Krugman, Nobel Prize winner for Economics, described it as "a volume really superb" and "an extraordinary work [...] certainly the most economic important book of the year if not the decade." In turn, Martin Wolf, one of the most influential writers on economic issues worldwide, says that the work of Piketty is "extremely important" and Branko Milanovic, a former World Bank economist, said it is "one of the primary work of economic thought ".